THE IMPACT OF GLOBALIZATION ON FOREST RESOURCES AND LOCAL COMMUNITIES - Leila Mahdavi; Ali Reza; Fatemeh Hashemi (Journal of Selvicoltura Asean, 2025)
Globalization has increasingly affected forest resources and local communities around the world. The growing demand for natural resources driven by global markets has led to both positive and negative consequences for forests and the people dependent on them. Forest ecosystems, crucial for biodiversity and climate regulation, are often threatened by logging, land conversion, and unsustainable practices associated with globalization. The interaction between economic development, environmental degradation, and local community livelihoods has become a critical area of study in sustainable development and environmental conservation. This study aims to examine the impact of globalization on forest resources and local communities, with a focus on both the challenges and opportunities arising from global economic integration. It seeks to understand how globalization influences forest degradation, conservation efforts, and the socio-economic conditions of indigenous and rural populations. The research employs a mixed-methods approach, combining qualitative case studies from various regions with quantitative analysis of forest resource depletion trends. Data were gathered from interviews with local communities, government reports, and forest resource databases. Statistical tools were used to analyze the correlation between globalization indicators (e.g., trade volumes, foreign investments) and deforestation rates. The study finds that while globalization has led to economic growth in some areas, it has also accelerated deforestation and degraded local ecosystems. Communities dependent on forests for livelihood have experienced both disruption of traditional practices and exposure to new economic opportunities. However, the benefits of globalization have been uneven, with wealthier communities often benefiting more than the most vulnerable. Globalization presents a complex challenge for forest resources and local communities. Sustainable solutions require a balance between economic development and environmental conservation, with inclusive policies that protect the interests of indigenous and rural populations.